1986
DOI: 10.1164/arrd.1986.133.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in Chronic Obstructive Pulmonary Disease1–3

Abstract: We recruited 985 patients with COPD but without hypoxemia or other serious disease, treated them in a standard fashion, and followed them closely for nearly 3 yr. At the time of recruitment the patients were carefully characterized as to symptom severity, lung function, exercise tolerance, and quality of life, and studies of lung function were repeated during follow-up. Overall mortality was 23% in 3 yr of follow-up. Patient age and the initial value of the FEV1 were the most accurate predictors of death; when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
264
5
20

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 722 publications
(303 citation statements)
references
References 0 publications
14
264
5
20
Order By: Relevance
“…The significance of PaCO 2 levels is more controversial. Several authors have found PaCO 2 to be a useful predictor of mortality [17, 20, 21], but other studies have not confirmed these results [18, 22]. The range of PaCO 2 in our series of patients was very narrow, the mean value being 40.4 mm Hg with a standard deviation of 3.1 mm Hg; the maximum value of PaCO 2 was 46 mm Hg (4 patients).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The significance of PaCO 2 levels is more controversial. Several authors have found PaCO 2 to be a useful predictor of mortality [17, 20, 21], but other studies have not confirmed these results [18, 22]. The range of PaCO 2 in our series of patients was very narrow, the mean value being 40.4 mm Hg with a standard deviation of 3.1 mm Hg; the maximum value of PaCO 2 was 46 mm Hg (4 patients).…”
Section: Discussioncontrasting
confidence: 68%
“…The degree of airway obstruction, expressed by FEV 1 , is well known to correlate with survival: the higher the FEV 1 value at the time of selection, the lower the risk of COPD-related death [17, 18, 19]. The significance of PaCO 2 levels is more controversial.…”
Section: Discussionmentioning
confidence: 99%
“…This could reflect the beneficial effect of LTOT in hypoxaemic patients in improving the survival into the same range as that of patients with a Pa,O 2 >8 kPa. ANTHONISEN et al [21] showed that oxygen therapy improved survival in patients with a Pa,O 2 7.3 kPa (55 mmHg) to the same level as in patients with a similar level of obstruction but without hypoxaemia (Pa,O 2 Š7.3 kPa). Randomized, controlled trials with welldefined groups of patients and an assessment of quality of life, healthcare consumption and costs are needed.…”
Section: Discussionmentioning
confidence: 97%
“…FEV1 is independently predictive of survival even when mildly impaired [21]. COOPER and HOWARD [22] have shown that deterioration in airway function continues despite LTOT and thus reduces survival.…”
Section: Discussionmentioning
confidence: 99%
“…In COPD patients, FEV 1 , age, PaCO 2 , cardiac disease, long duration of mechanical ventilation and body mass index have been reported as the main factors affecting mortality [2,3,4,5,19,20,21,22,23,24,25]. In our previous study involving COPD patients with hypercapnic respiratory failure, among the variables that were shown to influence mortality, there were the need for intubation and complications of invasive mechanical ventilation [6].…”
Section: Discussionmentioning
confidence: 99%